Red deer (Cervus elaphus) damage investigation in Foreste Casentinesi, Monte Falterona and Campigna National Park - RUSSO, CLAUDIA; RACANELLI VERONICA; CASAROSA LAURA; GENNAI ANDREA; D'AMICO CLAUDIA; MENCUCCI MARCO (2011)
The Foreste Casentinesi, Monte Falterona and Campigna National Park has an area of about 36,000 ha and is located along the Apennine ridge, between the regions of Emilia Romagna and Tuscany. The forest area is about 79%, while areas used for agriculture and grazing are about 7.5%. In the Park there are wild boar (Sus scrofa), fallow deer (Dama dama), red deer (Cervus elaphus), roe deer (Capreolus capreolus); the only predator is the wolf (Canis lupus). The most common deer is the red deer, an intermediate feeder being able to browse woody vegetation or graze grasslands. The aim of this study was to assess the damage from red deer, based on the damaged surface and on the compensation that the Park annually paid during years 2006-2008. We used a GIS system that allowed us to obtain data on damaged areas subdivided by crop types (pasture, meadow pasture, arable, orchards and chestnut groves); it has also been possible to locate the orchards and chestnut groves for which compensation was paid. The nocturnal observation, the height of browsing and removed foliage permitted to discriminate between damage from different species. Pasture, meadow pasture and arable were damaged by red deer only in the first two years of our investigations (2006: 3,400 ha; 2007: 26,590 ha) and only in the Tuscan side of the Park, while in the Emilian side damages were caused by all the other ungulate. Orchards and chestnuts groves, instead, have been damaged in three years always in the same areas of Tuscan side. Total annual compensations paid for pasture, meadow pasture, arable, orchards and chestnut groves were very low, respectively € 2,192 for 2006, € 694 for 2007 and € 350 for 2008. From this analysis, an enormous damage to the coppice together with the lack of compensation is also emerged; therefore the local Mountain Community requires a reduction of red deer population, creating a conflict with the purposes of the Park.